Medical students' communication skills in clinical education: Results from a cohort study. Issue 10 (October 2017) - Bachmann, Cadja; Roschlaub, Silke; Harendza, Sigrid; Keim, Rebecca; Scherer, Martin
Highlights: Our cohort study revealed severe communication deficiencies at graduation. Inappropriate history taking and communication skills causing costs became evident. Individual communication deficiencies could barely be eliminated over time. Patient-centeredness and empathy were rather low at graduation. Graduates are inadequately prepared for clinical practice regarding communication. Abstract: Objective: To assess students' communication skills during clinical medical education and at graduation. Methods: We conducted an observational cohort study from 2007 to 2011 with 26 voluntary undergraduate medical students at Hamburg University based on video-taped consultations in year four and at graduation. 176 consultations were analyzed quantitatively with validated and non-validated context-independent communication observation instruments (interrater reliability ≥0.8). Based on observational protocols each consultation was also documented in free-text comments, salient topics were extracted afterwards. Results: 26 students, seven males, were enrolled in the survey. On average, graduates scored higher in differential-diagnostic questioning and time management but showed deficiencies in taking systematic and complete symptom-oriented histories, in communication techniques, in structuring consultations and in gathering the patients' perspectives. Patient-centeredness and empathy were rather low at graduation. Individual deficiencies could barely be eliminated. Conclusion: Medical students were able to enhance their clinical reasoning skills and their time management. Still, various communication deficiencies in final year students became evident regarding appropriate history taking, communication skills, empathy and patient-centeredness. Practice implications: The necessity of developing a longitudinal communication curriculum with enhanced communication trainings and assessments became evident. A curriculum should ensure that students' communication competencies are firmly achieved at graduation.